Analysis of residential real estate market in Tbilisi - Rybalko, Grigoriy (2025)
This thesis investigates the determinants of residential real-estate price dynamics in Tbilisi, Georgia, over 2019–2024. A novel panel combining the National Statistics Office’s Residential Property Price Index with district-level transaction data from the National Agency of Public Registry provides annual observations for ten city districts. Price trends are described with index analysis, followed by Pearson correlations and district-specific bivariate OLS regressions linking year-on-year price growth to GDP growth, consumer-price inflation, policy interest rates and net migration. The findings imply that macro-economic expansion and inflationary conditions, rather than demographic shocks, dominated Tbilisi’s recent housing cycle. Policy implications include the need for counter-cyclical macro-prudential measures and accelerated housing supply to mitigate affordability pressures during future demand surges. The study enriches the limited empirical literature on housing markets in emerging post-Soviet economies and provides a reproducible framework for district-level analysis under severe data constraints.